As high as it gets: Ingroup projection processes in the superordinate group humans. (January 2016) - Reese, Gerhard; Berthold, Anne; Steffens, Melanie C.
Abstract: Recent research on inclusive identities suggests that the highly inclusive superordinate group "humans" is a relevant social category such that identification with all humans is related to various pro-social outcomes. In this research, we tested whether dual identity affects the extent to which the superordinate group humans serves as a relevant comparison standard for relations between developed and developing countries. Overall, participants from a developed country perceived their ingroup as more relatively prototypical for all humanity than people from developing countries. Study 1 revealed that relative prototypicality perceptions predicted weaker behavioral intentions to act against global inequality. In Studies 2 and 3, higher levels of relative prototypicality tended to predict fewer donations and a lower probability to seek fair trade information. Perceived legitimacy of global inequality explained the relation between relative prototypicality and donation behavior (Study 3). Dual identification with both developed countries and humanity did not predict relative prototypicality judgments. We discuss that the social representation of all humans can be a meaningful comparison standard for individuals, and we discuss the role of dual identity in international relations.